Caracterización de una correcta locución informativa en los medios audiovisuales - Rodero Antón, Emma (Estudios sobre el Mensaje Periodístico, 2007)
Voice is our main communication resource and the tool that it is used in greater proportion on audiovisual media. This is especially evident on radio, the sound media, but it is also used on television although to a lesser extent. So, even in the most basic bibliography about audiovisual media, the importance of the correct use of voice in the messages transmission is recognized. Nevertheless, years of little formation have caused the present presentation to be neither suitable nor correct. This is the reason for which we set out to realize a compendium of recommendations and defects analysis around the news presentation, based always on different empirical researches made in these years.